2022
DOI: 10.1038/s41598-022-10016-2
|View full text |Cite
|
Sign up to set email alerts
|

SAR and optical images correlation illuminates post-seismic landslide motion after the Mw 7.8 Gorkha earthquake (Nepal)

Abstract: In the days to weeks following an earthquake, landslides can display specific post-seismic motions, including delayed initiations and post-seismic relaxations. These motions have an uncertain origin, sometimes attributed to specificities of the landslide basal interface or to fluid transports in the landslide basal shear zone. Here we address this question, by documenting the co- and post-seismic motions of slow-moving landslides accelerated by the Gorkha earthquake (Mw 7.8, 25/04/2015, Nepal). We detect 11 sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 53 publications
7
26
1
Order By: Relevance
“…La Sorbella landslide (Italy), in turn, did not show any measurable increase in activity after coseismic displacements of 0.3-0.8 mm recorded during three earthquakes 13,14 . This large variation in the ratio between coseismic and postseismic motions has also been observed in various landslides affected by the Gorkha earthquake in Nepal 9 .…”
supporting
confidence: 67%
See 1 more Smart Citation
“…La Sorbella landslide (Italy), in turn, did not show any measurable increase in activity after coseismic displacements of 0.3-0.8 mm recorded during three earthquakes 13,14 . This large variation in the ratio between coseismic and postseismic motions has also been observed in various landslides affected by the Gorkha earthquake in Nepal 9 .…”
supporting
confidence: 67%
“…Of particular interest is the response to seismic shaking of active slow-moving landslides, which pose a serious threat to people and infrastructure [4][5][6][7][8] . Observations of such landslides reveal a wide range of earthquake related displacements, with surprisingly poor correlation between coseismic and postseismic motion 9 . For instance, the relatively small coseismic displacements (1-2 cm) of the Maca landslide (Peru) were followed by periods of increased velocities for about one month, resulting in three times greater cumulative displacements 10,11 .…”
mentioning
confidence: 99%
“…Such approach is not uncommon as previous studies have also utilised the LOS velocity for identifying active hillslopes (Bayer et al, 2018;Bekaert et al, 2020;Cheaib et al, 2022;Lacroix et al, 2022).…”
Section: Limitationsmentioning
confidence: 99%
“…However, owing to the high computational requirement of TS-InSAR techniques, regional scale analyses, in particular, associated with earthquakes, are still rare. For instance, Lacroix et al (2022) revealed the lagged initiations and post-seismic relaxations of slow-moving landslides in the area hit by the 2015 Gorkha earthquake using Sentinel-1 SAR data. During this post-seismic relaxation phase, slowmoving hillslopes were found to have accelerating deformation mainly because of groundwater transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Optical images conform to human vision, but are susceptible to objective factors such as cloud interference [2], whereas SAR images are immune to the imaging defects of optical images and have the advantages of all-weather acquisition, a long line of sight, and some level of penetration capability. Therefore, the fusion of optical and SAR images is widely used in pattern recognition [3], change detection [4], and landslide recognition [5]. However, a prerequisite for the fusion of SAR and optical images is high-accuracy matching.…”
Section: Introductionmentioning
confidence: 99%